Ancient Period Garden Park Art - Abbasova Mehriban; Abbasova Mehriban (Genius Journals, 2022)
The ancient kings of Iran created gardens near the huge palaces they built. The garden near the ancient palace of Persepolis is one such garden. According to the Indian scientist M. Randhawa, the Iranian king Cyrus II is the first ruler who built "charbogs" in Iran and Turan. One such garden was the garden created in the 6th century BC around Pasargad, the capital of ancient Iran
Keywords: Garden; charbogs; Gulnoma